Keputusan Menabung Nasabah Bank Syariah Indonesia KCP Palembang Sudirman Yang Dipengaruhi Oleh Literasi, Pemahaman Dan Promosi - Yuliana, Nana; Mail Hilian Batin; Abu Bakar Sidik (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
This research was conducted due to problems, namely the low knowledge and understanding of customers regarding Islamic banking products and the lack of effective promotions carried out by banks, causing low customer interest in saving. The purpose of this study was to determine the effect of literacy, understanding and promotion on the saving decision of customers of Bank Syariah Indonesia KCP Palembang Sudirman. The sampling technique used was purposive sampling method using the Slovin formula. The data analysis technique used is the classical assumption test, multiple linear regression analysis and hypothesis testing using the IBM SPSS Statistics 26 application tool. The results of this study indicate that literacy has a positive and significant effect on customers' saving decisions with a value of t count > t table (3,627 > 1,660) and a significance value of 0.000 <0.05, understanding that there is no effect on customer saving decisions with a t count <t table (1,210 <1,660) and a significance value of 0.229 > 0.05, promotions have a positive and significant effect on decisions saving customers with a t count > t table (8,203 > 1,660) and a significance value of 0.000 <0.05 and literacy, understanding and promotion have a joint effect on customer saving decisions with an F count > F table (65,264 > 2.31) and a significance value of 0.000 <0.05.